The ecology of juvenile Rhabdosargus holubi (Steinachner) (Teleostei : Sparidae) - Blaber, Stephen J M (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1974)
INTRODUCTION: Estuaries have received considerable attention from biologists in southern Africa in the past thirty years. Professor J.H. Day and the Zoology Department of the University of Cape Town have undertaken ecological surveys of a large number of estuaries of a variety of types, laying the important groundwork for more detailed studies of single species or problems. Their studies showed that the fish populations of southern African estuaries consist mainly of marine species. Why and when these species enter or leave the estuaries and whether they grow or breed in them were not established. The only relatively detailed study of a fish in southern African estuaries was that of Talbot (1955) who investigated aspects of the growth, feeding and reproduction of Rhabdosargus globiceps (Cuvier). No quantitative information has been published on any of the fish species, perhaps due to the difficulty of obtaining such data; results such as population estimates, mortality rates and growth rates are particularly unreliable when the area being investigated is in direct contact with the sea. Studies relating to even a single species of fish are hampered by immigration and emigration between estuary and sea, which make the population continuously variable. The larger estuaries are also difficult to sample adequately, especially with regard to netting, except perhaps on a very large scale using expensive commercial equipment. Along the southern African coast many of the smaller estuaries with a limited catchment area are cut off from the sea for most of the year due to erratic rainfall and longshore drift of sand. These closed or 'blind' estuaries of south eastern Africa, of which there are at least thirty in the eastern Cape Province, provide excellent areas for studying estuarine fish populations which enter when the estuary is open to the sea, but become isolated once it closes. These fish which become cut off in closed estuaries are subject to a new series of conditions. They are exposed to the wider temperature and salinity fluctuations of an estuary and they are forced to utilise the food resources of the estuary. Additionally they may be subjected to predation from piscivorous birds, and those predatory fish which are also cut off in the estuary. These factors will affect the size, mortality, and growth rates of a fish population. Since the fish are isolated no recruitment from the sea can take place, and any increase in numbers would have to come from breeding within the estuary. It is inevitable that the most numerous species should receive attention first. Rhabdosargus holubi (Steindachner) (Synonomy : Sargus holubi Stndr, Austrosparus tricuspidens Smith, Rhabdosargus tricuspidens (Smith))(Plate 1) is one of the most abundant fish in the estuaries of the eastern Cape Province. According to Smith (1965) it is endemic to southern Africa, occurring from the Cape to Zululand, being most common between Mossel Bay and East London. It is largely replaced by Rhabdosargus sarba (Forskal) in the north of its range and by Rhabdosargus globiceps (Cuvier) in the south. Commonly called the 'flatty' or silver bream it is considered only as being of nuisance value by fishermen, seldom exceeding 30 cm in length. In this study the ecology of R.holubi was examined in relation to the closed West Kleinemond estuary which is a small 'blind' estuary typical of those found along the eastern Cape coast. The growth, mortality and population size of R.holubi in this estuary were investigated and linked where possible with predation and detailed studies into the tolerances, food, and feeding of the species. It was not known at the commencement of the study whether breeding could occur in estuaries, although Smith (1965) stated that R.holubi does breed in estuaries. During the course of the sampling programme in the West Kleinemond estuary, measurements of the growth and population structure of two other species of fish were recorded for comparison with R.holubi: the sparid Lithognathus lithognathus (Cuvier) (White Steenbras) and the piscivorous carangid Hypacanthas amia (L.) (Leervis or garrick). Laboratory studies on R.holubi were possible due to the fact that large numbers of this species could be caught in eastern Cape estuaries and transported to Grahamstown, where they could be maintained in captivity for up to four months in recirculating seawater aquaria. During the course of the study over 2000 fish were kept in captivity at different times for a variety of experiments. Another 2500 were preserved for gut analyses and lipid determinations, while over 5000 were captured, examined and released in the field.
Keywords: Osteichthyes; Fishes -- Breeding; Fish populations; Fish culture -- South Africa; Estuaries -- South Africa -- Eastern Cape; Aquatic ecology